Dual HER2 blockade in the first-line treatment of metastatic breast cancer - A retrospective population-based observational study in Danish patients. (June 2020) - Christensen, Thomas; Berg, Tobias; Nielsen, Lise Birk; Andersson, Michael; Jensen, Maj-Britt; Knoop, Ann
Abstract: Objectives: Randomized clinical trials do not include a population that truly reflects a real-world population, due to their inclusion and exclusion criteria. This leads to concerns about the applicability of these studies in a clinical practice. In the present study, we aim to describe the clinical and demographic characteristics, treatment patterns, and clinical outcomes in a population of patients with HER2-positive metastatic breast cancer who received pertuzumab and trastuzumab as first-line treatment in a real-world setting. Methods: The database of the Danish Breast Cancer Group was used to assemble data on patients included in the period April 2013 to August 2017. The primary endpoints were overall survival (OS) and progression-free survival (PFS). Results: A cohort of 291 patients with a median age of 58 years was registered. Hereof 112 (38%) patients with de novo disease (primary disseminated) and 179 (62%) with recurrence. The median follow-up for OS was 24.1 months. The median OS was 41.8 months (95% CI, 37.7 to NE) and the median PFS was 15.8 months (95% CI, 14.0 to 19.9). For de novo patients alone, the median OS was not reached whereas the median PFS was 17.9 months (95% CI, 14.3 to 27.3). Hazard ratios for patients receiving vinorelbine showed comparable results as for the whole population. Conclusion: This heterogeneous patient population in a real-world setting had a PFS comparable with what could be expected from the related randomized trial. The de novo patients had better OS and PFS as compared to patients with recurrence. Highlights: Patients with HER2-positive metastatic breast cancer. Pertuzumab and trastuzumab as first-line treatment in a real-world setting. A cohort of 291 patients; 112 with de novo disease and 179 with recurrence. Median OS; 41.8 months and median PFS; 15.8 months. PFS comparable with what could be expected from the related randomized trial.